Cotidiano, práticas de apoio e intergeracionalidade em famílias de crianças com deficiência intelectual e de crianças com desenvolvimento típico: a ótica de três gerações - Yamashiro, Juliana Archiza (2013)
Literature has pointed to the importance of intergenerational relationships in families of children with and without disabilities. Once the familiar universe of a child goes beyond the interaction that he establishes with his mother, involving fathers, siblings, grandparents and other individuals, the focus of intergenerationality has contributed to the understanding of developmental processes and family adaptation in families of children with and without developmental abnormalities. Furthermore, studies indicate the need for greater understanding about the family s factors associated with stress reported by the elderly. The aim of this study was to identify the experiences of families of children with intellectual disabilities and typically developing children, about daily life, support practices and intergenerationality from the perspective of three generations - grandmothers, mothers and siblings. As the specific objectives we have: (1) assess the differences and similarities in patterns of intergenerational relationships and daily life of the two family groups represented, (2) identify the presence of stress in participant grandmothers. The study included 36 family members of 12 families of children with intellectual disabilities and typically developing children who were linked to public and / or philanthropic schools located in countryside of Sao Paulo - Brazil, who had older siblings and grandparents living in the same city. For data collection were used: 1) Identification questionnaire of the child and family, 2) Economic Classification Criterion Brazil (CCEB), 3) Semi-structured roadmap interviews for mothers, grandmothers and siblings of the children; 4) Inventory stress symptoms for adults (ISSL). The data obtained through the identification questionnaire, the CCEB and the ISSL were analyzed using descriptive statistics. The interviews were analyzed qualitatively using the technique of the Collective Subject Discourse. The main findings indicate that grandmothers of both family groups studied represent an important source of support for the family. Moreover, the intergenerational relationship between grandmothers and their older grandchildren presented as positive in the lives of all involved, with no significant differences between groups. However, in the case of families of children with disabilities, it was observed that the interaction between grandmothers and older grandchildren is increased with specific features of this reality, since the grandmothers seem to interfere more in the relationship between siblings than the grandmothers of typically developing children do. Furthermore, older siblings, in these families were identified as important support to their mothers and siblings with disabilities. About the stress experienced by the third generation, the results from the application of ISSL revealed that the majority of grandparents of children with disabilities are stressed, while only one grandmother of typically developing children showed symptoms of stress. It is argued about the contribution of intergenerational relationships in the development of all family members and is pointed up, in the case of grandmothers of children with disabilities, about the importance of considering them in the guidance and clarification about the issue of the child. It is emphasized on the importance of intergenerational studies and the need for education and health activities that promote and strength the intergenerational connections.